2014
DOI: 10.13070/rs.en.1.625
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of early sexual debut among men and women - a strong predictor of HIV and sexual risk in Malawi

Abstract: The 2010 Malawi Demographic and Health Survey (MDHS) is a large, nationally representative sample survey conducted by the National Statistical Office (NSO). The 2010 MDHS covered a total of 27,000 households, involving 24,000 female and 7,000 male respondents. The primary objective of the 2010 MDHS is to provide up-to-date information for policymakers, planners, researchers, and programme managers on fertility levels, nuptiality, fertility preferences, knowledge and use of family planning methods, breastfeedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study by Peltzer (2010) found mixed results with more boys (38.1%) than girls 15.8% who experience sexual debut before the age of 15 years. It has been evident that those who initiate sexual activities earlier exhibit a constellation of risk factors for sexually transmitted infections (Misiri, H. 2014), and are more likely not to use condoms at first sex. Victims of early sexual debut are prone to poor sexual health outcomes, early family formation, poor economic security, incarceration and few middle school interventions (Erkut et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Peltzer (2010) found mixed results with more boys (38.1%) than girls 15.8% who experience sexual debut before the age of 15 years. It has been evident that those who initiate sexual activities earlier exhibit a constellation of risk factors for sexually transmitted infections (Misiri, H. 2014), and are more likely not to use condoms at first sex. Victims of early sexual debut are prone to poor sexual health outcomes, early family formation, poor economic security, incarceration and few middle school interventions (Erkut et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Malawi have shown that most young people initiate sex at an early age before they get married, others initiate sex as early as 10 years, or before the age of 17 years (Maluwa- Banda and Lunguzi, 2002), and about 50% of youths in Malawi initiate sexual intercourse before the age of 15 (UNFPA, 2001). The median age at first sex among young men and women in Malawi ranges from 18 for males to 17 years for females (Misiri, H. 2014). In Nigeria, early sexual debut is a major health concern, especially among girls (Cortez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%